PERAN KONTROL DIRI DALAM MOTIVASI BERPRESTASI DAN PERFEKSIONISME TERHADAP PROKRASTINASI AKADEMIK - Yusuf Syaifulloh; Santi Susanti; Mardi Mardi (Universitas Tribhuwana Tunggadewi, 2021)
This reseach aims to examined the role of Self-Control as a mediating variable in the effect of Academic Perfection on Academic Procrastination. Quantitative method was used with data collection techniques by online questionnaire’s. Population in this research were students of Economics Education Faculty of Economics UNJ on 2013-2016 all concentration which they currently doing their S1 thesis. 145 people to be the sample were counted with proportional random sampling techniques. Techniques of data analysis used test for requirement analysis, test for hyphothesis and path analysis. The result of test for requirements analysis showed that data was normal and linearly distributed. Test for hypothesis result concluded all of them were accepted and path analysis result showed Self-Control was able to mediate dependents and independents variables. The ability of Achievement Motivation, Perfectionism and Self-Control to define Academic Procrastination are 31,4%, while the rest were influenced by other variables that are not used. From this research concluded that were need for developing interpersonal skill to avoid procrastination behavior specially on academic realm.